Een hoog IQ stelt late vermindering van cognitieve vaardigheden uit - Diesfeldt, Han F. A. (Tijdschrift voor Gerontologie en Geriatrie, 2017)
bespreking:Thorvaldsson V, Skoog I,Johansson B. IQ as moderator of terminal decline inperceptual and motor speed, spatial, and verbal ability:Testing the cognitive reserve hypothesis in a population-based sample followed from age 70 until death.Psychology and Aging. 2017;32:148–157